Comparison of the degree of microleakage in three restorative systems using universal adhesives: an in vitro study - Cahuayme Chávez, Antonio Rodrigo (2023)
Composite resins are the most widely used material for restorations in the last decade. An adhesive system is required to serve as a bonding agent between the tooth structure and the restoration, and universal adhesive systems are used. However, one of the main problems in restorations is microleakage, defined as the passage of bacteria or fluids between the restorative material and the prepared cavity. Objective: To compare the degree of microleakage between three restorative systems using universal adhesives before and after the thermocycling process. Material and methods: Experimental in vitro study with a sample of dental anterior pieces of 120 bovines. Three brands of restorative systems were used for class V restorations: 3M®, FGM®, and Ivoclar®. Each brand had a control group and an experimental group. The experimental groups were subjected to a thermocycling process. After that, the sample was immersed in methylene blue for 24 hours for subsequent cutting and observation under the microscope. Results: The Ivoclar® brand restorative system showed lower microleakage than the 3M® and FGM® brand restorative systems. The chi-square test showed a significant difference between the control and experimental groups. Conclusions: There is a significant difference in the degree of microleakage in Class V restorations using three restorative systems with universal adhesives before and after thermocycling.